Convergent close-coupling calculations of positron-magnesium scattering - Savage, Jeremy; Fursa, Dmitry; Bray, Igor (American Physical Society, 2011)
The single-center convergent close-coupling method has been applied to positron-magnesium scattering at incident energies from 0.01 to 100 eV. Cross sections are presented for elastic scattering and excitation of 3 1P, as well as for the total ionization and total scattering processes. We also provide an estimate of the positronium formation cross section. The results agree very well with the measurements of the total cross section by Stein et al. Nucl. Instrum. Methods Phys. Res. Sect. B 143 68 (1998)], and consistent with the positronium formation measurements of Surdutovich et al. Phys. Rev. A 68 022709 (2003)] for positron energies above the ionization threshold. For energies below the positronium formation threshold (0.8 eV) we find a large P-wave resonance at 0.17 eV. A similar resonance behavior was found by Mitroy and Bromley Phys. Rev. Lett. 98 173001 (2007)] at an energy of 0.1 eV.